2019
DOI: 10.3390/scipharm87040034
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Protective Role of Glucosamine against Osteoarthritis: Review of Its Molecular Mechanisms

Abstract: Osteoarthritis (OA) is a joint disease resulting from cartilage degeneration and causing joint pain and stiffness. Glucosamine exerts chondroprotective effects and effectively reduces OA pain and stiffness. This review aims to summarise the mechanism of glucosamine in protecting joint health and preventing OA by conducting a literature search on original articles. Current evidence has revealed that glucosamine exhibits anti-inflammatory effects by reducing the levels of pro-inflammatory factors (such as tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 131 publications
0
6
0
Order By: Relevance
“…Glucosamine induces tissue regeneration by enhancing stem cell proliferation, and chondrogenic and osteoblastic differentiation. 46 Furthermore, it increases the levels of anti-inflammatory cytokines (IL-2, IL-10), lowers p38 MAPK and c-JNK expression, increases extracellular-signal-regulated kinase (ERK1/2) expression, inhibits nuclear factor-kB (NF-kB) and nod-like receptor protein 3 ( NLRP3 ) inflammasome and caspase-1 activation. Glucosamine also possesses antioxidant properties.…”
Section: Prescription Glucosamine Sulfate Downregulates Key Genes Invmentioning
confidence: 99%
“…Glucosamine induces tissue regeneration by enhancing stem cell proliferation, and chondrogenic and osteoblastic differentiation. 46 Furthermore, it increases the levels of anti-inflammatory cytokines (IL-2, IL-10), lowers p38 MAPK and c-JNK expression, increases extracellular-signal-regulated kinase (ERK1/2) expression, inhibits nuclear factor-kB (NF-kB) and nod-like receptor protein 3 ( NLRP3 ) inflammasome and caspase-1 activation. Glucosamine also possesses antioxidant properties.…”
Section: Prescription Glucosamine Sulfate Downregulates Key Genes Invmentioning
confidence: 99%
“…Glucosamine (2-amino-2-deoxy-D-glucose) is an amino monosaccharide with essential roles in the biochemical synthesis of glycosylated proteins and lipids [1]. Intensive studies have proved that the exogenous use of glucosamine can relieve osteoarthritis (OA) symptoms and restore articular functions [2][3][4][5]. It also has many antiinfammatory and antioxidative efects with minimal adverse impact on human health [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional pharmacological agents for OA, such as intra-articular corticosteroid and hyaluronan injections, as well as oral analgesics, focus on symptomatic relief [6,7]. Glucosamine sulphate, a substrate for the synthesis of proteoglycans, is a commonly used alternative treatment for OA [8]. Numerous meta-analyses have found that glucosamine Life 2023, 13, 2343 2 of 19 sulphate may reduce OA pain while having only minor effects on patients' knee functions [9,10].…”
Section: Introductionmentioning
confidence: 99%